International Journal of Pharmacy Practice (Royal Pharmaceutical Society)
Accès par la licence nationale : https://revue-sommaire.data.istex.fr/ark:/67375/8Q1-40VS208C-S de 1991 à 2016
Keywords: Pharmacologie